'Valuing Life Itself': On Radical Environmental Activists' Post-Anthropocentric Worldviews. (December 2020) - Alberro, Heather
The present era of biological annihilation lends significant urgency to the need to radically reconfigure human–animal–nature relations along more ethical lines and sustainable trajectories. This article engages with largely post-humanist scholarship to offer up an in-depth qualitative analysis of a set of semi-structured interviews, conducted in August 2017–2018 with 26 radical environmental activists (REAs) from a variety of movements. These activists are posited as contemporary manifestations of the 'post-anthropocentric paradigm shifts' that challenge traditional notions of human separateness from – and superiority to – the nonhuman world. However, despite being broadly categorised as post-humanist or post-anthropocentric in their efforts to deconstruct hierarchical and dualistic constructions of the human–animal–nature relationship, considerable variations abound in terms of who and what REAs value and on what basis. The article concludes with a brief discussion of the nature of REAs' post-anthropocentric sensibilities and mobilisations, and considers implications for the development of more ethical modes of human– animal–nature relationality that value and respect the irreducible alterity of nonhuman others.